(3JfbjM GdefGXQ dPhi GdCHUGQ hGdHUGFQs - (3ceGd GdOjf CHh GdMSf GdaGQSis; (3GHf GdgjKe , eMeO Hf GdMSf Hf GdgjKe, CHh Ydj HWdjehS GdKGfj,J (B430 (3g` s
(3ChdgG (B:s
(3GdMeO ddg fhQ GdGfhGQ heXgQ YLGFH GdCSQGQhHYO NGa Ydi ef JfhQ Ybdg hRcG aQYg s
(3BNQgG (B:s
(3hdG jbJUQ ai GdEYJHGQGJ GdeTGQ ZdjgG Ydi eQI Ch eQJjf aEfg ZPG CcKQ GdeYGhOI jJMbjb GdCcHQ adfNJe GdcJGH MGeOjf Gddg SHMGfg hJYGdi s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B83 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B225s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3Gdadcs